The Application of Vinamidinium Salt to the Synthesis of 3-Chloro-α-carbolines - Tian, Shaixiao; Mao, Yu; Jiang, Yongjun; Xu, Guangyu (Synlett, 2018)
A convenient synthesis of 3-chloro-α-carbolines by the condensation of vinamidinium salt with 2-indolinones via two steps is reported. This protocol has the advantages of readily available starting materials, high yields and easy workup.
Keywords: α-carboline; 3-chloro-α-carboline; synthesis; vinamidinium salt; 2-indolinone